HUBUNGAN KUALITAS LINGKUNGAN FISIK RUMAH DAN PERILAKU KESEHATAN DENGAN KEJADIAN TB PARU DI WILAYAH KERJA PUSKESMAS GONDANGLEGI KECAMATAN GONDANGLEGI KABUPATEN MALANG - Saffira Kusuma Anggraeni; Mursid Raharjo; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2015)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by Mycobacterium tuberculosis which most commonly occurs in the lungs but may infect any part of the body. There were 31 pulmonary tuberculosis patients in Gondanglegi Health Center in 2012 and 31 patients in 2013, there were 27 patients with positive AFB in 2012 and 24 patients in 2013. The total number of patients from January to June 2014 were 10 patients. The prevalence of pulmonary TB was found to 103 per 10.000 population with 48% of case detection rate (CDR) in 2013. The purpose of this study is to determine  the relationship between the quality of home physical environment and health behavior with pulmonary tuberculosis incidence in a work area of Gondanglegi health center Gondanglegi subdistrict Malang regency. This research is an Analytical Observational study that use Case Control study. The study population was 70 people, consisted of 35 case population (pulmonary TB sufferers which was recorded on Gondanglegi Health Center's book from January 2013 to February 2014) and 35 control population (people lived near the sufferers' home). 60 samples consisted of 30 case samples (Positive AFB) and 30 control samples (negative AFB) using Purposive Sampling method. Data analysis used  Chi-Square test with 95% confidence interval. The result showed that variables related to pulmonary TB incidence were ventilation (p=0,0001; OR = 15,167; 95% CI = 4,09 – 56,248), home humidity (p=0,002; OR = 6,417; 95% CI = 2,084 – 19,755), light intensity (p=0,0001; OR = 26,000; 95% CI = 6,532 – 103,498), and smoking habits (p=0,0001; OR = 16,429; 95% CI = 4,569 – 56,073). In other hand, unrelated variables consisted of floors types (=0,595; OR = 1,529; 95% CI= 0,536 - 4,361), walls types (p=1,000; OR = 0,857; 95% CI = 0,288 - 2,547), residential density (p=1,000; OR = 0,8; 95% CI = 0,215 – 2,972), and temperature (p=0,531; OR = 1,818; 95% CI = 0,518 – 6,382). The conclusion of this study, there is relationship between ventilation, home humidity, light intensity and smoking habits with pulmonary TB.